Enhanced electrochemical performance of LiNi0.6Co0.2Mn0.2O2 cathode at high cutoff voltage by modifying electrode/electrolyte interface with lithium metasilicate. (20th August 2017) - Fu, Jiale; Mu, Daobin; Wu, Borong; Bi, Jiaying; Liu, Xiaojiang; Peng, Yiyuan; Li, Yiqing; Wu, Feng
Highlights: The electrochemical properties of the LiNi0.6 Co0.2 Mn0.2 O2 cathode are investigated at high voltage of 4.6 V. The Li2 SiO3 suppresses the decomposition of LiPF6 and carbonate solvents. Li2 SiO3 helpfully retards the transition metal dissolution by consuming HF. The enhanced electrochemical properties of the LiNi0.6 Co0.2 Mn0.2 O2 cathode mixed with Li2 SiO3 . Abstract: Developing high-voltage Li ion batteries (LIBs) is an important trend to meet the requirement of high energy density battery. However, high voltage will cause a series of problems harming the cycle performance of LIBs at the same time. This work is to investigate the effect of inorganic substance Li2 SiO3 on the electrochemical performance of LiNi0.6 Co0.2 Mn0.2 O2 (NCM622) cathode at high cutoff voltage of 4.6 V. XRD result shows that the structure of NCM622 cathode material is not affected by mixing Li2 SiO3 . However, XPS and EIS tests indicate that Li2 SiO3 has an evident influence on suppressing the decomposition of LiPF6 and carbonate solvents at high voltage, reducing interfacial solid film impedance and modifying electrode/electrolyte interface. In addition, Li2 SiO3 retards the transition metal dissolution by consuming HF. Therefore, it enhances the electrochemical properties of the NCM622 cathode significantly. The highest discharge capacity increases to 191.7 mA h g -1 by mixing Li2 SiO3, compared with the value of 180 mA h g -1 in the case of NCM622 cathode. The NCM622 electrode mixed with Li2 SiO3 also exhibits a better capacity retention of 73.4% after 200 cycles and a high rate capability at 20C with the value of 89 mA h g -1, in contrast with 62.2% and 31 mA h g -1 attained in the NCM622 cathode.